Servier v Commission: following in the footsteps of Lundbeck - Richard Tepper (UCL Journal of Law and Jurisprudence, 2019)
To download this paper please click https://discovery.ucl.ac.uk/id/eprint/10086919 In 2009, the European Commission’s Competition Inquiry into the Pharmaceutical Sector focused on the competitive relationship between originator companies and generic undertakings. The Commission discovered that patent settlement agreements containing a reverse transfer of value from the originator to the generic undertaking were used to delay entry of generics into markets, limit consumers’ choices, and burden public budgets. Since the Inquiry, the Commission adopted a more aggressive enforcement approach towards these patent settlements. In the recent Servier decision, it determined that the relevant agreements were in breach of Articles 101 and 102 TFEU. This commentary assesses the merits of Lundbeck’s general rule on reverse payment settlements, evaluates the General Court’s review of that decision in Servier and the exemption created for licensing agreements, and illustrates the difficulties in defining the relevant market for pharmaceutical products.